A flexible memristive model with simplex basis function. (14th July 2016) - Yu, Juntang; Xi, Xiangming; Wang, Shuning
Summary: In this paper, we propose a flexible memristive model with simplex basis function. In the memristive model, a piecewise window function is applied to limit the physical range of the state variable, and a piecewise linear model (called simplex basis function model) is applied to describe the integral function of the current and charge. The expression of the state variable and the memristance can be almost analytically obtained. Thus, some serious errors occurring in the simulations of some existing memristive models can be avoided. The proposed memristive model shows great flexibility due to the good approximation capability of the simplex basis function model. Copyright © 2016 John Wiley & Sons, Ltd.